Centring localised indigenous concepts of wellbeing in urban nature-based solutions for climate change adaptation: case-studies from Aotearoa New Zealand and the Cook Islands - Mihaere, Shannon; Holman-Wharehoka, Māia-te-oho; Mataroa, Jovaan; Kiddle, Gabriel Luke; Pedersen Zari, Maibritt; Blaschke, Paul; Bloomfield, Sibyl (Frontiers in Environmental Science, 2024)
Nature-based solutions (NbS) offer significant potential for climate change adaptation and resilience. NbS strengthen biodiversity and ecosystems, and premise approaches that centre human wellbeing. But understandings and models of wellbeing differ and continue to evolve. This paper reviews wellbeing models and thinking from Aotearoa New Zealand, with focus on Te Ao Māori (the Māori world and worldview) as well as other Indigenous models of wellbeing from wider Te Moana-nui-a-Kiwa Oceania. We highlight how holistic understandings of human-ecology-climate connections are fundamental for the wellbeing of Indigenous peoples of Te Moana-nui-a-Kiwa Oceania and that they should underpin NbS approaches in the region. We profile case study experience from Aotearoa New Zealand and the Cook Islands emerging out of the Nature-based Urban design for Wellbeing and Adaptation in Oceania (NUWAO) research project, that aims to develop nature-based urban design solutions, rooted in Indigenous knowledges that support climate change adaptation and wellbeing. We show that there is great potential for nature-based urban adaptation agendas to be more effective if linked closely to Indigenous ecological knowledge and understandings of wellbeing.Author Contributions SM, MH and JM lead authorship, supported by GLK. MPZ, PB and SB equal supporting input.We would like to acknowledge funding from the Marsden Fund -Royal Society of New Zealand.